2020
DOI: 10.1002/lipd.12213
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Hexadecynoic Acid Isomers toward Clinical Isolates of Multidrug‐Resistant Staphylococcus aureus

Abstract: In the present study, the structural characteristics that impart antibacterial activity to C16 alkynoic fatty acids (aFA) were further investigated. The syntheses of hexadecynoic acids (HDA) containing triple bonds at C‐3, C‐6, C‐8, C‐9, C‐10, and C‐12 were carried out in four steps and with an overall yield of 34–78%. In addition, HDA analogs containing a sulfur atom at either C‐4 or C‐5 were also prepared in 69–77% overall yields, respectively. Results from this study revealed that the triple bond at C‐2 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The mechanism of FA regulation on the gut microbiota is summarized in Table S5. According to the gene regulation, 2-hexadecynoic acid (C16:1) showed the inhibitory activity of DNA gyrase, which is responsible for DNA replication during bacterial growth . Linoleic acid (C18:2) has inhibitory activity on the binding activity of the DNA-binding protein ToxT, thereby inhibiting the activation of the key virulence genes encoding cholera toxin (CT) and toxin-coregulated pilus (TCP) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of FA regulation on the gut microbiota is summarized in Table S5. According to the gene regulation, 2-hexadecynoic acid (C16:1) showed the inhibitory activity of DNA gyrase, which is responsible for DNA replication during bacterial growth . Linoleic acid (C18:2) has inhibitory activity on the binding activity of the DNA-binding protein ToxT, thereby inhibiting the activation of the key virulence genes encoding cholera toxin (CT) and toxin-coregulated pilus (TCP) .…”
Section: Resultsmentioning
confidence: 99%
“…According to the gene regulation, 2hexadecynoic acid (C16:1) showed the inhibitory activity of DNA gyrase, which is responsible for DNA replication during bacterial growth. 31 Linoleic acid (C18:2) has inhibitory activity on the binding activity of the DNA-binding protein ToxT, thereby inhibiting the activation of the key virulence genes encoding cholera toxin (CT) and toxin-coregulated pilus (TCP). 32 In addition, linoleic acid can inhibit the peptidoglycan synthesis gene in the bacterial cell wall and interact with 2hexadecanoic acid to selectively inhibit the Fabi (nutrient component synthesis protein) of pathogens.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Synthetic uFAs can directly kill multi-drug resistant bacteria at very low concentrations (i.e., at micromolar and/or nanomolar levels). 6,7 Many reports address the antibacterial properties of synthetic uFA against Gram-positive bacteria. [6][7][8][9] For example, Konthikamee et al reported the antibacterial activity of 2-alkynoic FA against Gram-positive bacteria, including Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Many reports address the antibacterial properties of synthetic uFA against Gram-positive bacteria. [6][7][8][9] For example, Konthikamee et al reported the antibacterial activity of 2-alkynoic FA against Gram-positive bacteria, including Staphylococcus aureus. 8 In 2014, Sanabria et al performed the first study to determine the structural characteristics needed to prepare antibacterial 2alkynoic FA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation